2015
DOI: 10.1002/cncr.29224
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of cetuximab and lapatinib in patients with advanced solid tumor malignancies

Abstract: Background Acquired resistance to anti-EGFR therapy may be due to EGFR-ErbB2 heterodimerization and pathway reactivation. In pre-clinical studies. inhibiting ErbB2 blocked this resistance mechanism and re-sensitized cells to anti-EGFR therapy. Cetuximab targets the EGFR receptor, whereas lapatinib inhibits both EGFR and ErbB2. We conducted a phase I trial to assess the safety, dose-limiting toxicities (DLTS), and maximum-tolerated dose (MTD) of cetuximab and lapatinib in patients with solid tumors. Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Furthermore, Siena et al reported that trastuzumab and lapatinib combination therapy induced a partial response in seven of 22 patients (32%) with HER2-positive CRC who were resistant to anti-EGFR antibody therapy [ 24 ]. Additionally, Deeken et al reported that the combination of cetuximab and lapatinib provided a partial response in some patients with CRC who were resistant to anti-EGFR antibody therapy [ 25 ]. Therefore, these data suggest that evaluation of HER2 in ctDNA may be helpful for determining the optimal therapy involving HER2-targeting combination therapy rather than anti-EGFR antibodies alone in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Siena et al reported that trastuzumab and lapatinib combination therapy induced a partial response in seven of 22 patients (32%) with HER2-positive CRC who were resistant to anti-EGFR antibody therapy [ 24 ]. Additionally, Deeken et al reported that the combination of cetuximab and lapatinib provided a partial response in some patients with CRC who were resistant to anti-EGFR antibody therapy [ 25 ]. Therefore, these data suggest that evaluation of HER2 in ctDNA may be helpful for determining the optimal therapy involving HER2-targeting combination therapy rather than anti-EGFR antibodies alone in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with HER2 amplification were resistant to anti-EGFR antibody therapy, other treatment strategies, including lapatinib or trastuzumab, can overcome cetuximab resistance in CRCs [ 242 ]. Finally, in addition to the previously reported trial conducted by Siena et al [ 244 ], Deeken et al [ 248 ] concluded that the combination of cetuximab and lapatinib provided a partial response in some patients with CRC who were resistant to anti-EGFR antibody therapy.…”
Section: Bespoke Treatment: Role Of Biomarkers In Clinical Settingmentioning
confidence: 86%
“…Yonesaka K et al[ 5 ] demonstrated that inhibiting HER2 signaling in HER2 - amplified colon cancer models could restore their sensitivity to EGFR monoclonal antibody in vitro and in vivo . Moreover, an HER2-positive mCRC patient who underwent anti-EGFR therapy responded well to lapatinib plus cetuximab[ 15 ]. Therefore, the inhibition of both HER2 and EGFR is another potential strategy to treat HER2-positive and RAS/BRAF wild-type mCRC.…”
Section: Discussionmentioning
confidence: 99%